Physicochemical properties of honeybee pollen enriched acidophilus milk and probiotic yoghurt - Glušac Jovana R.; Stijepić Milka J.; Milanović Spasenija D.; Đurđević-Milošević Dragica M. (Acta Periodica Technologica, 2015)
The aim of this work was to examine the possibility of preparation of acidophilus milk and probiotic yoghurt by processing of milk (1%, 2.8% and 3.2% w/w fat) enriched with honeybee pollen (0.6% w/w). The quality of produced fermented milks was followed by comparing pH value during fermentation and storage time, as well as of lactic acid content and sensory properties during 14 days of storage. Fermentation time was influenced more the type of the starter culture than by honeybee pollen addition or fat level. The addition of honeybee pollen increased the production of lactic acid, regardless of the fat level. The effects of different starters (L. acidophilus LA-5, S. thermophilus and L. Delbrueckii ssp. bulgaricus) on the production of lactic acid were also different, but not as obvious as that due to pollen addition. The obtained results revealed that honeybee addition had positive effects on the physicochemical and sensory properties of produced acidophilus milk and probiotic yoghurt.